Tricky interview questions - UK Physical Sciences Centre; University of Hull (The University of Hull)
This is a flash animation giving about some potential tricky interview questions. This is one of a series of 11 flash animations as part of a larger employability resource pack. Feedback on the use of this resource is welcomed so please email psc@hull.ac.uk with your comments.